Effect of Irrigation Scheduling and Nutritional Levels on Yield and Water Productivity of Green Chilli (Capsicum annuum L.) in a Coastal Soil of West Bengal - Ranajit Panda; Sanmay Kumar Patra; Anshuman Das; Bappa Paramanik; Bisweswar Mahato; Debraj Saha; Asim Biswas (Journal of the Indian Society of Soil Science, 2024)
India, as the world’s largest producer, consumer, and exporter of chilli, contributes approximately 40% to the global chilli production, with an area of 760.98 thousand hectares dedicated to its cultivation and an annual yield of 1605.01 thousand metric tonnes. This study, conducted in the salt-affected coastal region of West Bengal, which encompasses about 1.7448 million hectares (27.7% of the state’s land area), aimed to investigate the impact of various irrigation schedules and integrated nutritional levels on the yield and water use efficiency of green chilli. An experimental field study was carried out in Akshwanagar village, Kakdwip block, South 24 Parganas district, employing a factorial randomized block design with three replications. The experiment included three levels of irrigation (I1: Branching + Flowering, I2: Branching + Flowering + Fruiting, I3: Vegetative + Branching + Flowering + Fruiting) and four nutrient management practices (F1: 100-60-60 NPK kg ha-1, F2: 75-45-45 NPK kg ha-1, F3: 50-30-30 NPK kg ha-1+ 10 tonnes ha-1 of farmyard manure, F4: 50-30-30 NPK kg ha-1 + 5 tonnes ha-1 of vermicompost). The study found that different irrigation schedules, when integrated with varying levels of nutritional management, significantly influenced the yields and yield-contributing parameters of green chilli. The results indicated that the lowest yield of 9.32 tonnes ha-1 was obtained with a two-stage irrigation schedule at the branching and flowering stages, while a moderate yield of 10.03 tonnes ha-1 was resulted from a three-stage irrigation schedule encompassing the branching, flowering, and fruiting stages. Notably, an increase in water use efficiency was observed with a decrease in water application. This research provides crucial insights into optimizing water and fertilizer nutrient requirements for chilli cultivation in coastal saline soils, offering a significant contribution to the sustainable agricultural practices and economic evaluation under varying irrigation and nutrient conditions. The findings have broad implications on chilli production in similar agro-climatic regions, prevail within India as well as other part of the world.